Joana Paula de Morais: história, memória e trajetórias educativas (1900-1963) - Xavier, Antônio Roberto (2014)
This is a research to Doctoral Thesis in History and have, like general scope, understand and while explain the History and Education Memory from the educational trajectories implemented by laic educator Joana Paula Morais in not-formal places of teaching and learning, in period from 1900 to 1963. The problematic glimpsed is anchored in the deficit of local researches in the field of not-formal education and in the conventional totalitarian view of brazilian education history, like if this history contemplate an homogeneity in all the spaces and contexts of the nation in the periods of Colony, Monarchy and Republic. Methodologically, it is a research of historical-biographical character of qualitative nature with the use of written sources and oral sources, through field research. In field research, the techniques used were open or direct interviews with the spontaneous participation of the social subjects. In this perspective, sought to the historical context reconstruction and it on situation add to a peculiar critical balance, therefore its considered this is a sine qua non condition inside a critical constructive view. It is considered valuable in the historical researches the transporting, through the contextualizationat at time the analyzed facts have given. However, knowing to that the reconstruction the past of events as it is only something speculative and/or approach. What can be made is revisit them with the help of the sources avaliable to come afloat part to this reality lived and felt. As neither everything is written and neither the documents involve all the stories and memories and, understanding that the official traditional history, at least until the 1970s, prioritized the written sources of political history and of the great figures, it resort to a methodological resource of the oral history as a trusted source of credibility considered neither greater or of less importance. (THOMPSOM, 1992; XAVIER, 2010).Therefore, it was recorded interviews with relatives, past pupils and/or contemporaries that belongs to the studied context or near it or even that it know any anuncement something related to educator Joana Paula de Morais and her educational practices in the period of her material existence and educational activities. The theoretical basis it concentrated, among others in: Barros (2011); Martinho Rodrigues (2008, 2009, 2010, 2012); Dosse (2003); Nietzsche (1986, 1987, 1992 and 2003); Abbagnano (1998); Thompson (1992); Bergson (1999); Bossi (1994); Burke (2009); Le Goff (1976, 1994, 1996); Carretero (2010); Ricoeur (2007); Vasconcelos Júnior (2006); Vasconcelos and Magalhães Júnior (2001; 2013); Vasconcelos et al. (2002, 2009, 2010, 2011; 2012, 2013); Machado (2010); Machado; Vasconcelos; Vasconcelos Júnior (2011); Andrade (2010, 2011); Bezerra (2006); Manacorda (2006); Saviani (2011, 2008, 2005); Durkheim (1978); Vieira (2002); Jucá (2003, 2013); Bessa et. al. (2001); Villa (2000); Meneses (1991-2); Barroso (2004) and the narratives of the social subjects interviewed.